The Students’ Difficulties in Speaking English: A Case Study at SMPN 3 Mataram - Nisa Cahyani; Amrullah; Dewi Satria Elmiana; Muhammad Amin (Journal of English Education Forum (JEEF), 2026)
Abstract: This study aimed to investigate the difficulties faced by seventh-grade students in speaking English at SMPN 3 Mataram. The research employed a qualitative case study design. The participants consisted of fifteen students from two classes. Data were collected through classroom observations and semi-structured interviews to obtain in-depth information about students’ speaking difficulties. The data were analyzed using data reduction, data display, and conclusion drawing techniques. The findings revealed that students experienced various linguistic and non-linguistic difficulties in speaking English. The results showed that the main linguistic difficulties included limited vocabulary, incorrect pronunciation, and grammatical errors, which caused hesitation and lack of fluency during speaking activities. In addition, psychological factors such as low confidence, anxiety, fear of making mistakes, and fear of being laughed at by peers were identified as the most dominant factors affecting students’ speaking performance. Classroom observations also indicated that students frequently relied on their first language when they lacked English vocabulary. Therefore, it can be concluded that both linguistic and psychological factors significantly influence students’ speaking ability, and teachers are encouraged to apply supportive strategies, provide positive feedback, and create a comfortable classroom atmosphere to improve students’ speaking skills.